Tai Chi exercise and functional electrical stimulation of lower limb muscles for rehabilitation in older adults with chronic systolic heart failure: a non-randomized clinical trial - Hao,Yi (2019)
Exercise-based training decreases hospitalizations in heart failure patients but such patients have exercise intolerance. The objectives of the study were to evaluate the effect of 12 weeks of Tai Chi exercise and lower limb muscles' functional electrical stimulation in older chronic heart failure adults. A total of 1,084 older adults with chronic systolic heart failure were included in a non-randomized clinical trial (n=271 per group). The control group did not receive any kind of intervention, one group received functional electrical stimulation of lower limb muscles (FES group), another group practiced Tai Chi exercise (TCE group), and another received functional electrical stimulation of lower limb muscles and practiced Tai Chi exercise (FES & TCE group). Quality of life and cardiorespiratory functions of all patients were evaluated. Compared to the control group, only FES group had increased Kansas City Cardiomyopathy Questionnaire (KCCQ) score (P<0.0001, q=9.06), only the TCE group had decreased heart rate (P<0.0001, q=5.72), and decreased peak oxygen consumption was reported in the TCE group (P<0.0001, q=9.15) and FES & TCE group (P<0.0001, q=10.69). FES of lower limb muscles and Tai Chi exercise can recover the quality of life and cardiorespiratory functions of older chronic heart failure adults (trial registration: Research Registry 4474, January 1, 2015).